Heterogeneity of the Type I Interferon Signature in Rheumatoid Arthritis: A Potential Limitation for Its Use As a Clinical Biomarker - Rodríguez-Carrio, Javier; Alperi-López, Mercedes; López, Patricia; Ballina-García, Francisco J.; Suárez, Ana (Frontiers in Immunology, 2018)
Introduction: increased expression of interferon-responding genes (IRGs), the so-called IFN signature, has been reported in RA. However, some controversy exists concerning its clinical relevance. The main aim of this study was to evaluate whether quantitative and qualitative differences in the activation of the IFN pathway may account for these findings. Methods: expression of IFI44, IFI44L, IFI6 and MX1 was determined in peripheral blood in 98 RA patients and 28 controls. RA patients were classified into groups according to their clinical stage and treatments received: very early RA (VERA), bDMARD-naïve and bDMARD. An additional group of 13 RA patients candidates for TNFa-blockade was also recruited. The associations among IRGs were evaluated by network and principal component analyses. Results: the expression of all IRGs was increased in RA to different levels. The IFN score was increased in all RA groups (VERA, bDMARD-naïve and bDMARD), but important differences in their degree of activation and in the relationships among IRGs were observed. The IFN score correlated the accumulated DAS28 and it was found to be a predictor of clinical outcome in VERA. No differences in the IFN score were observed between the bDMARD-naïve and bDMARD groups, but opposite associations with the clinical parameters were noted. Interestingly, the correlations among IRGs delineate different pictures between these two groups. The IFN score at baseline predicted poor clinical outcome upon TNF-ablockade. Although no absolute changes in the IFN score were found, TNFa-blockade shifted the associations among IRGs. Conclusions: a certain heterogeneity within the IFN signature can be recognized in RA, depending on the clinical stage. The structure of the IFN signature may be a potential explanation for the controversy in this field and must be considered to decipher its clinical relevance in RA.